Optimization of Parameters Using Taguchi Orthogonal Array Design for an Intensified Per-Pass Conversion of Alphabutol® Technology in Butene-1 Production - Hamoud Alenezi; Zainab Haidar; Mirdul Das (International Journal of Chemical Engineering)
Taguchi orthogonal design was used in this study to investigate the effects of three operational parameters (i.e., reactor temperature, reactor pressure, and catalyst ratio on per-pass conversion (PPC)). The optimal PPC was calculated from the predicted response function at 48°C of reactor temperature, 21 kg/cm2g of reactor pressure, and catalyst mole ratio of 2.50. Under these conditions, the PPC was estimated to be 87.1 per cent, with a maximum SNR of 38.95. In line with the delta ranking, the decreasing order of significance of each process parameter on the average per-pass conversion (PPC) was x1 > x2 > x3, with percentage contributions of 50.6%, 26.1%, and 23.3% for reactor temperature, temperature, and catalyst mole ratio, respectively. The optimal production condition can therefore be attained at a larger scale with the higher per-pass conversion of butene-1.